2017
DOI: 10.1093/infdis/jix322
|View full text |Cite
|
Sign up to set email alerts
|

Histone Methyltransferase SET8 Epigenetically Reprograms Host Immune Responses to Assist Mycobacterial Survival

Abstract: NQO1 and TRXR1 are important host reductases implicated in the regulation of inflammation and apoptosis. Although the transcriptional machinery governing these processes have been extensively investigated, the associated epigenetic regulatory events remain unclear. Here, we report that SET8, a histone H4 lysine 20 monomethylase (H4K20me1), is highly induced during Mycobacterium tuberculosis infection that orchestrates immune evasion strategies through the induction of NQO1 and TRXR1 in vivo. SET8, along with F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 47 publications
0
31
0
Order By: Relevance
“…There is also evidence that SET8 may function as a barrier to mitochondrial oxidative phosphorylation activity [38]. SET8 was found to induce NQO1, a reductase that inhibits inflammation and apoptosis in cells [39]. Our previous study indicated that SET8 aggravated glycolytic metabolism and thus induced HCC progression [40].…”
Section: Discussionmentioning
confidence: 96%
“…There is also evidence that SET8 may function as a barrier to mitochondrial oxidative phosphorylation activity [38]. SET8 was found to induce NQO1, a reductase that inhibits inflammation and apoptosis in cells [39]. Our previous study indicated that SET8 aggravated glycolytic metabolism and thus induced HCC progression [40].…”
Section: Discussionmentioning
confidence: 96%
“…This aligns with the observation that cells with high cholesterol upregulate anti-oxidants such as NRF2 and HO-1 to mitigate oxidative stress 74 . A recent report from our lab proposes that mycobacterial clearance pathways such as apoptosis and pro-inflammatory cytokine production are hampered by classical anti-oxidative molecules TRXR1 and NQO1 5 . Therefore, cholesterol-dependent antioxidant production and subsequent innate and adaptive immune alterations not reported as yet, can potentially help in strengthening the understanding of the survival strategies employed by Mtb.…”
Section: Discussionmentioning
confidence: 99%
“…; SET8 HMT governs immune processes such as apoptosis, oxidative stress and cytokine secretion 5 ; while certain mycobacterial proteins themselves gain access to host chromatin and modulate a plenitude of immune genes 6 . One of the classical features of tuberculosis (TB) infection involves the accumulation of neutral lipids, cholesterol and cholesteryl esters to generate foamy macrophage (FM) phenotype 7,8 .…”
Section: Mhc-ii Presentationmentioning
confidence: 99%
“…A recent review by van der Heijden et al (2018) appraised the role and significance of epigenetic modifications in innate immune cells to establish trained immunity (van der Heijden et al, 2018). Infection with Mtb, an intracellular pathogen which prefers to reside in alveolar macrophages, has been shown to induce epigenetic changes in the host cell, i.e., modification of histones 3 and 4 acetylation patterns to promote its prolonged survival (Esterhuyse et al, 2015;Moores et al, 2017;Singh et al, 2017). Furthermore, Mtb also triggers the synthesis of host microRNA species to modulate immune responses to its benefit (Iannaccone et al, 2014;Huang et al, 2015;Kumar et al, 2015;von Both et al, 2018).…”
Section: Macrophages and Dendritic Cellsmentioning
confidence: 99%